MATERNAL BLOOD LOSS BY EXPANSION OF UTERINE INCISION AT CAESAREAN SECTION-A COMPARISON BETWEEN SHARP AND BLUNT TECHNIQUES - Hameed, Nazli; Ali, Mohammad Asghar (Journal of Ayub Medical College Abbottabad, 2004)
Background: In order to minimize intra operative blood loss during caesarean section, two techniques of expansion of uterine incision (sharp versus blunt) while performing lower segment transverse caesareans deliveries and their effect upon intraoperative blood loss were studied. Moreover, each method was also compared for its inadvertent extension of uterine incision laterally or into the broad ligament, into the cervix or vagina. Method: A quasi-experimental study with convenient sampling, involving two groups of women who underwent lower transverse segment Cesarean section. Both groups were studied for their demographic characteristics and clinical data. Standard surgical techniques were used in both groups except the expansion of uterine incision, either by sharp or blunt methods. Finally a comparison of two groups was made regarding blood loss, change in haematocrit, blood transfusion and uterine tears. The study was conducted at Combined Military Hospital Rawalpindi during May 2002 to April 2003. Results: No significant difference was found between the two groups regarding their demographic characteristics and clinical data. Intraoperative blood loss and post-operative hematocrit drop were more significant in the patient group in which a blunt uterine incision was made. Besides, more patients in this group received blood transfusions. Unintended extension of uterine (tears) was also significantly higher in this group. Conclusion: Sharp expansion of uterine incision during low segment caesarean section is safer and precise based on these results. Key words: Caesarean section, surgical techniques, uterine incision.